2007
DOI: 10.1074/jbc.m607432200
|View full text |Cite
|
Sign up to set email alerts
|

Tel2 Is Required for Activation of the Mrc1-mediated Replication Checkpoint

Abstract: Proteins belonging to the Tel2/Rad-5/Clk-2 family are conserved among eukaryotes and are involved in various cellular processes, such as cell proliferation, telomere maintenance, the biological clock, and the DNA damage checkpoint. However, the molecular mechanisms underlying the functions of these molecules remain largely unclear. Here we report that in the fission yeast, Schizosaccharomyces pombe, Tel2 is required for efficient phosphorylation of Mrc1, a mediator of DNA replication checkpoint signaling, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 73 publications
(99 reference statements)
4
51
0
Order By: Relevance
“…The TEL2/ CLK2 orthologs in C. elegans and the budding yeast S. cerevisiae are important regulators of telomere length (Runge and Zakian 1996;Kota and Runge 1999;Benard et al 2001;Lim et al 2001). In mammals and the fission yeast Schizosaccharomyces pombe, TEL2/CLK2 has been heavily implicated in the ATR signaling pathway and the S-phase checkpoint (Collis et al 2007(Collis et al , 2008Shikata et al 2007;Danielsen et al 2009). The connection between TEL2 and the PIKK family helps explain the pleiotrophic nature of the phenotypes of TEL2 mutants in different organisms.…”
mentioning
confidence: 99%
“…The TEL2/ CLK2 orthologs in C. elegans and the budding yeast S. cerevisiae are important regulators of telomere length (Runge and Zakian 1996;Kota and Runge 1999;Benard et al 2001;Lim et al 2001). In mammals and the fission yeast Schizosaccharomyces pombe, TEL2/CLK2 has been heavily implicated in the ATR signaling pathway and the S-phase checkpoint (Collis et al 2007(Collis et al , 2008Shikata et al 2007;Danielsen et al 2009). The connection between TEL2 and the PIKK family helps explain the pleiotrophic nature of the phenotypes of TEL2 mutants in different organisms.…”
mentioning
confidence: 99%
“…This study by Mordes et al (2008) has also reiterated the role of ATRIP in stabilizing the interaction between TopBP1 and ATR for ATR activation, illustrating the involvement of ATRIP in multiple steps of ATR regulation. However, some common regulation may exist among PIKKs, as suggested by the finding that the Tel2 protein can regulate the stability of all PIKK family members via interaction with conserved N-terminal HEAT repeats (Shikata et al 2007;Takai et al 2007). In some cases, these regulatory mechanisms can even functionally connect family members.…”
Section: Specificity In Pikk Activationmentioning
confidence: 99%
“…Subsequent studies in many organisms have demonstrated a conserved role for Tel2 in the DNA damage checkpoint response. [2][3][4][5] The absence of recognizable domains in Tel2 has been a major hindrance in understanding how it is able to operate at the molecular level. The discovery that S. pombe and mammalian Tel2 interact directly with all phosphatidylinositol 3-kinase related protein kinase (PIKK) family members (which include ATM, ATR, DNA-PKcs, mTOR, FRAP and SMG1) raised the possibility that Tel2 may act as a universal regulator of the PIKK family of kinases.…”
Section: Differential Regulation Of the Pikk Kinase Family By Tel2mentioning
confidence: 99%
“…The discovery that S. pombe and mammalian Tel2 interact directly with all phosphatidylinositol 3-kinase related protein kinase (PIKK) family members (which include ATM, ATR, DNA-PKcs, mTOR, FRAP and SMG1) raised the possibility that Tel2 may act as a universal regulator of the PIKK family of kinases. [3][4][5] A recent study has shown that conditional loss of Tel2 in mouse embryonic fibroblast (MEF) cells results in the dramatic reduction in protein levels of all PIKK family members. 5 This finding led de Lange and colleagues to propose that Tel2 is a highly conserved regulator of PIKK stability.…”
Section: Differential Regulation Of the Pikk Kinase Family By Tel2mentioning
confidence: 99%
See 1 more Smart Citation